Examining the Expression of miR-205 and CEA mRNA in Peripheral Blood of Patients with OSCC(Oral Squamous Cell Carcinomas) and Comparing them with Healthy People - Nazarian, Ameneh; Mohamadnia, Abdolreza; Danaee, Elham; Bahrami, Naghmeh (Asian Pacific Journal of Cancer Biology, 2019)
Introduction: Cancer is one of the most important causes of mortality in the world. So, in this study the changes of expressing miR-205 and CEA in oral cancer in peripheral blood were examined for early detection and better treatment. Methods: In this study, we selected the number of 30 patient people and 30 healthy people. We measured their blood miR-205 and CEA using Real-Time PCR technique and evaluated the relationship between the expression of these biomarkers with tumor staging and cancer progression. Findings: there is no a significant difference in mean age by comparing these two groups using t-test. The CEA mRNA biomarker was positive in 24 out of 30 people of the patient people group and was positive in 4 out of 30 people of the healthy people group. Statistical comparison represented a statistically significant difference between the two groups (P-value <0.001). The miR-205 biomarker was positive in 9 out of 30 people of the patient people group and was positive in 22 out of 30 people of the healthy people group. Statistical comparison represented a statistically significant difference the two groups (P-value <0.001). Conclusion: In general, the research result can be considered as a screening test for early detection of the disease in the early stages. It is recommended to conduct more extensive studies with larger sample sizes to further proof of the research results.